1998
DOI: 10.1161/01.str.29.8.1584
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Brain Natriuretic Peptide in Patients With Subarachnoid Hemorrhage

Abstract: Background and Purpose-Hyponatremia after subarachnoid hemorrhage (SAH) is commonly associated with diuresis and natriuresis, but the causes are still controversial. We investigated whether brain natriuretic peptide (BNP) was related to such hyponatremia. Methods-Plasma BNP concentrations were measured by immunoradiometric assay in 18 patients at 0 to 2 days (period 1), 7 to 9 days (period 2), and Ͼ14 days (period 3) after SAH. Plasma concentrations of antidiuretic hormone (ADH), atrial natriuretic peptide (AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 20 publications
4
57
2
4
Order By: Relevance
“…Increased plasma concentrations of a natriuretic polypeptide released from the brain have been reported (Yamanoto et al, 1987;Berendes et al, 1997) in patients with CSWS. A recent study showed increased circulating plasma brain natriuretic peptide concentrations in patients with CSWS following subarachnoid haemorrhage (Tomida et al, 1998). The pathophysiology of CSWS is not yet fully established, however, and although increased plasma concentrations of natriuretic peptides may be responsible for the natriuresis and hyponatraemia, the mechanism behind the increased secretion has not been identi®ed.…”
Section: Hypovolaemic Hyponatraemiamentioning
confidence: 99%
“…Increased plasma concentrations of a natriuretic polypeptide released from the brain have been reported (Yamanoto et al, 1987;Berendes et al, 1997) in patients with CSWS. A recent study showed increased circulating plasma brain natriuretic peptide concentrations in patients with CSWS following subarachnoid haemorrhage (Tomida et al, 1998). The pathophysiology of CSWS is not yet fully established, however, and although increased plasma concentrations of natriuretic peptides may be responsible for the natriuresis and hyponatraemia, the mechanism behind the increased secretion has not been identi®ed.…”
Section: Hypovolaemic Hyponatraemiamentioning
confidence: 99%
“…Initially, the effects of BNP on fluid and salt balance were explored. 4,24,27 Later, BNP and vasospasm were studied. Results from these studies indicated that it was the clinically apparent brain ischemia, rather than the angiographic or transcranial Doppler defined vasospasm, that was associated with the BNP increase.…”
mentioning
confidence: 99%
“…Troponin I (Tn-I) is elevated in approximately 20-30% of patients with the peak level within 1-2 days from the onset of SAH (21,24). Serum level of the brain natriuretic peptide (BNP) was also found to be increased soon after SAH and returning to baseline in 1 to 2 weeks (34). Increased BNP level is a predictor of worse neurologic outcomes and early in-hospital mortality (36).…”
Section: Resultsmentioning
confidence: 99%